2014
DOI: 10.4304/tpls.4.4.743-749
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus-based Comparative Study of Lexical Proficiency of Writings by Majors of Arts v.s. Those of Science

Abstract: With aids of corpus linguistics technology, WordSmith Tools, Range, and other software such as Coh-Metrix, this paper attempts to give a scientific analysis on lexical proficiency of writings in placement test for vocational college majors of arts and those of science. First, there exist huge lexical proficiency discrepancies between the students, and they should be implanted more stylistic knowledge in writing and be input more original English materials to enlarge their English vocabulary size. Second, those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Both sexes have difficulties in writing a narrative text with proficiency in the different areas of grammar. However, this study also found out that females are a bit higher than males in grammar proficiency, which is the same as the findings of the study conducted by Lange, Euler, and Zaretsky (2016) and Zhang (2014), indicating that girls have higher language competence than boys. The results indicate that STEM and SPA students with high level of grammar proficiency have committed minimal errors in writing their narrative texts.…”
Section: Level Of Grammar Proficiencysupporting
confidence: 89%
See 4 more Smart Citations
“…Both sexes have difficulties in writing a narrative text with proficiency in the different areas of grammar. However, this study also found out that females are a bit higher than males in grammar proficiency, which is the same as the findings of the study conducted by Lange, Euler, and Zaretsky (2016) and Zhang (2014), indicating that girls have higher language competence than boys. The results indicate that STEM and SPA students with high level of grammar proficiency have committed minimal errors in writing their narrative texts.…”
Section: Level Of Grammar Proficiencysupporting
confidence: 89%
“…Using the Scheffe method, the table of multiple comparisons revealed that STEM significantly differed with STVEP and regular, which means that the sequencing skills of the STEM students are better than the sequencing skills of STVEP and regular students. Abelman (2004) and Zhang (2014) have also found the same results. Both investigated the sequencing skills of the students from special and non-special classes.…”
Section: Difference In the Level Of Sequencing Skillssupporting
confidence: 66%
See 3 more Smart Citations